PROFESSIONAL COMPETENCE AND TEACHERS’ CHALLENGES IN KONAWE KEPULAUAN REGENCY: A QUALITATIVE EXPLORATION - Rum, Jalaluddin; Zur, Sarjaniah; Anselah, Suman; Hakim, Miftahur Rahman; Zainal, Muhammad Asrianto (JURNAL EDUSCIENCE, 2026)
Purpose –This study aims to explore how teachers' professional competencies are implemented and sustained in island territories, with a particular focus on professional development practices, reflective processes, and the challenges of maintaining learning performance.Methodology – This study uses a qualitative case study design with a exploratory orientation. Data were collected through semi-structured interviews with teachers, school principals, and education supervisors. The interview guide consisted of open-ended questions focusing on teachers’ professional competence, digital challenges, emotional pressures, and work performance. Data were analyzed using a hybrid thematic analysis that combined deductive coding and inductive coding.Findings—Teachers' professional competence in Konawe Kepulauan is demonstrated through adaptive, practice-oriented strategies rather than through formal professional achievements. Teachers participate in professional development activities suited to their specific contexts, with support from school principals and supervisors. Nevertheless, formal professional development initiatives, including classroom action research and academic publications, are largely lacking. Teachers' professional practices are limited by digital and structural barriers, substantial workloads, and emotional stress, all of which influence their instructional decisions and overall performance.Contribution—The findings suggest that policymakers and school leaders reconceptualize professional development frameworks by recognizing reflective practice, peer collaboration, and adaptive teaching strategies as legitimate forms of sustainable professional competence in an island context.